2005
DOI: 10.1038/nbt1102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and culture of human embryonic stem cells

Abstract: Human embryonic stem cells have been defined as self-renewing cells that can give rise to many types of cells of the body. How and whether these cells can be manipulated to replace cells in diseased tissues, used to screen drugs and toxins, or studied to better understand normal development, however, depends on knowing more about their fundamental properties. Many different human embryonic stem cell lines--which are pluripotent, proliferate indefinitely in vitro and maintain a normal, euploid karyotype over ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
251
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(260 citation statements)
references
References 104 publications
8
251
0
1
Order By: Relevance
“…Genetic evaluation of therapeutic hESC E. Stephenson et al damage caused by reactive oxygen species and free radicals, which are generated during normal oxidative cell metabolism. Indeed, undifferentiated hESCs have a much lower expression of Cu/Zn-superoxide dismutase, glutathione peroxidase 1, and peroxiredoxin 1 and 2, which are enzymes that normally protect cells against such damage (Cho et al 2006 (Draper et al 2004;Hoffman & Carpenter 2005;Mitalipova et al 2005). Comparison of mechanical cutting of colonies and the use of enzymes for passage in the same hESC line suggested that mechanical cutting better supports maintenance of a normal karyotype in long-term culture; the enzyme-treated cell line was more likely to develop karyotype abnormalities (most often chromosome 12 and 17 trisomy).…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…Genetic evaluation of therapeutic hESC E. Stephenson et al damage caused by reactive oxygen species and free radicals, which are generated during normal oxidative cell metabolism. Indeed, undifferentiated hESCs have a much lower expression of Cu/Zn-superoxide dismutase, glutathione peroxidase 1, and peroxiredoxin 1 and 2, which are enzymes that normally protect cells against such damage (Cho et al 2006 (Draper et al 2004;Hoffman & Carpenter 2005;Mitalipova et al 2005). Comparison of mechanical cutting of colonies and the use of enzymes for passage in the same hESC line suggested that mechanical cutting better supports maintenance of a normal karyotype in long-term culture; the enzyme-treated cell line was more likely to develop karyotype abnormalities (most often chromosome 12 and 17 trisomy).…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…Moreover, certain sensitive cell types, such as human embryonic stem cells (hESCs) die or differentiate under restrictive metabolic conditions (7,11). To this end, Van hoof et al (7) sought to compensate for arginine to proline conversion in SILAC experiments by advocating the use of isotopically labeled arginine ( 15 N 4 -Arg) in light SILAC media as well as ( 15 N 4 -13 C 6 -Arg) in the heavy media.…”
mentioning
confidence: 99%
“…This is labor-intensive and time-consuming, and it normally generates variable cluster size and results in inconsistent cell distribution. On the other hand, enzymatic passaging dissociates the hESC colonies using enzymes such as animal-derived collagenase, dispase, and trypsin [39], xeno-free recombinant enzyme [16] or enzyme-free cell dissociation buffer [40], allowing a relatively consistent and standardized passaging of hESC. In view of clinical applications, enzymatic passaging is advantageous since it enables large-scale expansion of hESC.…”
Section: Clonal Derivation Of Hescmentioning
confidence: 99%